2021
DOI: 10.1016/j.scs.2021.103182
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, internet, and mobility: The rise of telework, telehealth, e-learning, and e-shopping

Abstract: This study provides new evidence on changes in a range of online activities due to the Coronavirus disease (COVID-19) pandemic. Online activities replaced physical participation in activities and contributed to changes in urban mobility during the pandemic. Using data from a nationwide survey in Greece, the paper examines changes in the importance and the frequency of engaging in online activities before and during COVID-19. Findings show that both the importance and the frequency of engaging in telework, tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(149 citation statements)
references
References 67 publications
(92 reference statements)
5
96
0
5
Order By: Relevance
“…The results show that COVID-19 encourages consumers to shop online [ 53 ]. Mouratidis Kostas et al (2021) used the data of the Greek national survey to study the importance and frequency of participating in online activities before and during COVID-19 [ 54 ]. The outbreak of COVID-19 has encouraged residents to make online consumption, increased the frequency of online shopping, and changed consumption habits.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that COVID-19 encourages consumers to shop online [ 53 ]. Mouratidis Kostas et al (2021) used the data of the Greek national survey to study the importance and frequency of participating in online activities before and during COVID-19 [ 54 ]. The outbreak of COVID-19 has encouraged residents to make online consumption, increased the frequency of online shopping, and changed consumption habits.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in traveler behavior in the pandemic additionally support the opportunity to promote sustainable means of transport. However, the question of the share of passenger cars in modal split remains, having in mind its individual character ( Mouratidis and Papagiannakis, 2021 ). Even though there are studies that analyzed the changes in the transport system during the various phases of the pandemic ( Shakibaei et al, 2021 ), it is very hard to fully predict the influence of COVID-19 on the future development of transport systems.…”
Section: Introductionmentioning
confidence: 99%
“…Many people have shifted from traditional office-working to teleworking, and online shopping has witnessed its apogee (Shamshiripour et al, 2020). For example, Mouratidis and Papagiannakis (2021) found that in Greece, 1 substantial increases were reported with respect to the frequencies of teleconferencing (57% increase), video calls with family or friends (55% increase), online learning (53% increase), and telework (49% increase). Such dramatic increases in e-activities have also been observed in many other countries.…”
Section: E-activitymentioning
confidence: 99%